Are our sub-centers prepared enough to tackle high-risk pregnancies? A cross-sectional survey from Southern Rajasthan, India - Paliwal, Bharti; Sharma, Rupa; Rao, Rajath (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. Sub-centers (SC) are the first contact point with the community with auxiliary nurse midwife (ANM) as the instrument, delivering all the primary health care services. The SCs are under constant criticism for their inability to deliver quality services. This study assessed the preparation of facilities available at the SC to manage high-risk pregnancies (HRP) and to compare the same between rural and tribal blocks of the selected district. Material and methods. This health facility-based cross-sectional observational study was done for 6 months among 276 rural and tribal SC of the Udaipur district by a two-stage random sampling method using an observational checklist to assess the infrastructure and logistics of SCs. Data were analyzed using SPSS 20. Results. The study covered 264 (95.7%) non-24x7 SCs and 12 (4.3%) 24x7 SCs. Only one-third SCs, 93 (33.6%) were situated at the center of the village. Only 151 (54.7%) SCs had attached ANM quarters. All 24x7 SCs and 78.4% of non-24x7 SCs had adequate equipment and infrastructure. Conclusion. Most of the subcentres’ infrastructure and functional equipment was equipped to tackle HRP. Rural SC adhered more than tribal. Most HRPs were tracked and referred to higher centers. Unless we emphasize strengthening SCs, the dream of a healthy nation will remain obscure.
Institutional Ethical Committee, RNT Medical College and MB General Hospital has been taken for the study (RNT/Stat/IEC/2017/167).
Keywords: auxiliary nurse-midwifery; high-risk pregnancy; primary health care; subcentres